2023
DOI: 10.3390/foods12020424
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus bisporus Polysaccharides Ameliorates Behavioural Deficits in D-Galactose-Induced Aging Mice: Mediated by Gut Microbiota

Abstract: White button mushroom polysaccharide (WMP) has various health-promoting functions. However, whether these functions are mediated by gut microbiota has not been well explored. Therefore, this study evaluated the anti-aging capacity of WMP and its effects on the diversity and composition of gut microbiota in D-galactose-induced aging mice. WMP significantly improved locomotor activity and the spatial and recognition memory of the aging mice. It also alleviated oxidative stress and decreased the pro-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
5
1
Order By: Relevance
“…52 Parabacteroides have also been linked to the aging process. In several aging studies, a significant decrease in Parabacteroides was observed in D-gal-induced models, [53][54][55] suggesting that Parabacteroides may be negatively correlated with the aging process. The specific function remains elusive and requires further investigation.…”
Section: Ark Clams Modulate Gut Microbiota Composition In Aging Rats ...mentioning
confidence: 99%
“…52 Parabacteroides have also been linked to the aging process. In several aging studies, a significant decrease in Parabacteroides was observed in D-gal-induced models, [53][54][55] suggesting that Parabacteroides may be negatively correlated with the aging process. The specific function remains elusive and requires further investigation.…”
Section: Ark Clams Modulate Gut Microbiota Composition In Aging Rats ...mentioning
confidence: 99%
“…The intracellular zinc polysaccharides (IZPs) of G. frondosa not only decreased the MDA content but also ameliorated the anile condition of D-galinduced-aging mice [53]. It was also shown that the sulfated polysaccharides of the golden mushroom Flammulina velutipes (SFPs) reversed the D-gal-induced weight loss and tissue damage of aging mice [54], and the polysaccharides of the common cultivated mushroom Agaricus bisporus (WMPs) improved the locomotor activity and spatial and recognition memory of the aging mice [55]. Interestingly, WMPs extracted by different methods such as acidic-extraction (AcAPs) and enzyme-assisted extraction (EnAPs) all displayed potential anti-aging effects against D-gal-induced-aging diseases on the liver, kidney, brain and skin [56,57].…”
Section: Fungal Polysaccharidesmentioning
confidence: 99%
“…Polysaccharides can be entirely fermented by the intestinal microbiota and increase the number of probiotic bacteria, ultimately benefiting healthy aging. WMPs were reported to significantly improve the locomotor activity and spatial and recognition memory of aging mice by both alleviating oxidative stress and decreasing pro-inflammatory cytokine levels, as well as increasing the short-chain fatty acid (SCFA) level and abundance of the beneficial bacteria Bacteroides and Parabacteroides [55]. FLAPs and FHSPs were demonstrated to prolong the lifespan of C. elegans by improving the antioxidant defense system and enriching specific gut bacteria (Romboutsia and Weissella) and metabolites [51].…”
Section: Intestinal Flora Regulationmentioning
confidence: 99%
“…There is a plethora of evidence suggesting that not only do polysaccharides have vital energy-related functions, but also participate in cell growth, division and regeneration [6]. For example, polysaccharides have been demonstrated to exhibit antibacterial [7] and antioxidant properties [8], lower blood pressure and sugar levels [9][10], reduce anti-aging [11], anti-radiation [12], and used as probiotics [13] [14]to promote a healthy immune system. There is a plethora of scienti c evidence supporting the importance of a healthy intestinal micro ora in human health.…”
Section: Introductionmentioning
confidence: 99%